Overload of families taking care of elderly people with Alzheimer's Disease: a comparative study - Ana Carla Borghi; Vivian Carla de Castro; Sonia Silva Marcon; Lígia Carreira (Universidade de São Paulo, 2013)
OBJECTIVE: to compare the overload of the main and secondary family carers of patients with Alzheimer's Disease, and identify which dimension generates most impact. METHOD: a comparative study conducted in the city of Maringá, State of Paraná, with 20 primary carers of elderly patients with Alzheimer's Disease and 20 secondary caregivers. The data was collected in May and June 2012, using the Scale for Assessment of Overload of Members of Psychiatric Patients' Families (FBIS-BR), and the results were analysed using the Mann-Whitney test and analysis of variance. RESULTS: the global objective overload, and also in each subscale, was significantly greater in the group of main caregivers; the subjective overload showed no difference between the groups. Comparing the subscales, the routine assistance provided to the patient had greater influence on objective overload in both groups, and the concern with the elderly patient was the dimension that had most influence on the subjective overload of main caregivers and also of secondary caregivers. CONCLUSION: the differences in overload between the different groups reinforces the need for planning of health care actions for each type of caregiver, seeking to reduce these differences.